2, 2′:6′, 2′′-Terpyridine-functionalized redox-responsive hydrogels as a platform for multi responsive amphiphilic polymer membranes. Issue 100 (13th October 2016) - Schöller, Katrin; Toncelli, Claudio; Experton, Juliette; Widmer, Susanne; Rentsch, Daniel; Vetushka, Aliaksei; Martin, Colin J.; Heuberger, Manfred; Housecroft, Catherine. E.; Constable, Edwin C.; Boesel, Luciano F.; Scherer, Lukas J.
Abstract : Amphiphilic polymer co-networks were functionalized with spyropiran and terpyridine yielding multi-responsive membranes with switchable properties and potential applications in drug delivery and medical sensors. Abstract : Nanophase-separated amphiphilic polymer co-networks are ideally suited as responsive membranes due to their stable co-continuous structure. Their functionalization with redox-responsive 2, 2′:6′, 2′′-terpyridine–metal complexes and light-responsive spiropyran derivatives leads to a novel material with tunable optical, redox and permeability properties. The versatility of the system in complexing various metal ions, such as cobalt or iron at different concentrations, results in a perfect monitoring over the degree of crosslinking of the hydrophilic poly(2-hydroxyethyl acrylate) channels. The reversibility of the complexation, the redox state of the metal and the isomerization to the merocyanine form upon UV illumination was evidenced by cyclic voltammetry, UV-Vis and permeability measurements under sequential conditions. Thus, the membrane provides light and redox addressable functionalities due to its adjustable and mechanically stable hydrogel network.